Teaching Inpatient Bedside Presenter Empowerment Actions During an Interactive Workshop - Sarah Hoffmann Vepraskas; Kelsey Porada; Jennifer Hadjiev; Sara Lauck; Heather Toth; Michael Weisgerber (Association of American Medical Colleges, 2018)
Introduction Medical students and interns are the principal communicators during inpatient bedside patient- and family-centered rounds. Excellent presenters are able to share information during rounds in a manner that is accurate, effective, and easy for all to understand. We previously identified the behaviors of excellent presenters and developed a term for them: presenter empowerment actions. Methods To promote the use of presenter empowerment actions, an interactive workshop was created to teach them to medical students and interns. This educational summary contains information on how to facilitate a workshop to promote presenter empowerment actions, which includes both a didactic presentation and an interactive game. Results Interns reported increases in confidence and knowledge of empowerment actions, as well as strong intent to incorporate presenter empowerment actions during inpatient rounds. Discussion A workshop with an interactive game is an effective way to teach empowerment actions to learners. To reinforce presenter empowerment action use after the workshop, we recommend direct observation using the Suspected Observable Presenter Empowerment Action Checklist to provide formative feedback to the presenters.